2013
DOI: 10.1523/jneurosci.5866-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Infarct-Derived Chondroitin Sulfate Proteoglycans Prevent Sympathetic Reinnervation after Cardiac Ischemia-Reperfusion Injury

Abstract: Sympathetic nerve can regenerate after injury to re-innervate target tissues. Sympathetic regeneration is well documented after chronic cardiac ischemia, so we were surprised that the cardiac infarct remained denervated following ischemia-reperfusion (I-R). We used mice to ask if the lack of sympathetic regeneration into the scar was due to blockade by inhibitory extracellular matrix within the infarct. We found that chondroitin sulfate proteoglycans (CSPGs) were present in the infarct after I-R, but not after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(87 citation statements)
references
References 65 publications
2
85
0
Order By: Relevance
“…Therefore, it is plausible that the reinnervation process starts in the epicardium. Furthermore, blocking of sympathetic nerve regeneration by inhibitory components of the extracellular matrix has recently been reported [8]. The presence of endocardial nontransmural scar tissue may be one factor contributing to the inhibition of further nerve growth towards the distal endocardial portion of the ventricle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is plausible that the reinnervation process starts in the epicardium. Furthermore, blocking of sympathetic nerve regeneration by inhibitory components of the extracellular matrix has recently been reported [8]. The presence of endocardial nontransmural scar tissue may be one factor contributing to the inhibition of further nerve growth towards the distal endocardial portion of the ventricle.…”
Section: Discussionmentioning
confidence: 99%
“…In animal experimental studies, temporal damage to the cardiac sympathetic nerves after transient ischemia has been shown [6][7][8][9][10][11][12][13]. In humans, several imaging studies using radiolabeled norepinephrine analog tracers have confirmed sympathetic nerve alterations, which are correlated with the area of ischemia in acute coronary syndrome [14].…”
Section: Introductionmentioning
confidence: 97%
“…Interestingly, whereas NGF stimulates axon growth, its precursor, proNGF, triggers axon degeneration (Nykjaer et al, 2004) and may be involved in post-MI denervation (Siao et al, 2012). Recently, Gardner and Habecker (2013) also identified chondroitin sulfate proteoglycans, which are present in reperfused infarcts, as responsible for chronic denervation observed in reperfused post-MI hearts.…”
Section: Ventriclementioning
confidence: 99%
“…It is thought that increases in nerve growth factor (NGF) are primarily responsible for hyperinnervation (Cao et al, 2000a) and blocking NGF prevents nerve sprouting following MI (Hasan et al, 2006). Conversely, sympathetic denervation is also associated with ventricular arrhythmia (Boogers et al, 2010; Fallavollita et al, 2014) and occurs in MI, diabetic neuropathy, and heart failure (Gardner and Habecker, 2013; Gardner et al, 2015; Jacobson et al, 2010; Kimura et al, 2010). Interestingly, whereas NGF stimulates axon growth, its precursor, proNGF, triggers axon degeneration (Nykjaer et al, 2004) and may be involved in post-MI denervation (Siao et al, 2012).…”
Section: Ventriclementioning
confidence: 99%
“…Other ECM signals with inhibitory effects for sympathetic axons may also be involved. For example, chondroitin sulfate proteoglycans have been shown recently to prevent sympathetic reinnervation after cardiac ischemia-reperfusion injury (Gardner and Habecker, 2013). It is also unknown whether other estrogen-regulated inhibitory signals, such as cell adhesion molecules, transmembrane signals and diffusible signals anchored to the ECM remain present in the frozen myometrial tissue sections and whether these signals may contribute to the diminished ability of the myometrial substrate to support sympathetic neurite outgrowth in vitro .…”
Section: Molecular Mechanisms Of Reproductive Tract Neuroplasticitymentioning
confidence: 99%